Influence of Organizational Culture, Success Context, and Ict Strategy on Organizational Performance, And Their Implications on Sustainable Competitive Advantage (Empire Study at LPP TVRI Jakarta) - Oscar Jayanagara; Darmanto Darmanto; Meita Istianda (Budapest International Research and Critics University, 2022)
This research aims to analyze the effect of Organizational Culture, Top Succession Context, and Information Communication Technology Strategy on Organizational Performance, and their implications to Sustained Competitive Advantage.The methodology of this research was quantitative research with hypothesis testing for examining seven hypotheses. Populations was the LPP TVRI Jakarta, which was located in DKI Jakarta, with sample size were 260 television workers. Data for this study were collected using questionnaires and SEM (Structural Equation Modeling) was employed for data analysis techniques. The results of this research in general there was the effect of Organizational Culture, Top Succession Context, and Information Communication Technology Strategy on Organizational Performance, Top Succession Context, Information Communication Technology Strategy, and Organizational Performance on Sustained Competitive Advantage LPP TVRI Jakarta. All of ten hypotheses which proposed in this research, eight hypotheses were being given can be accepted, except Organizational Culture did not influence Sustained Competitive Advantage. Information Communication Technology Strategy as an independent variable was the strongest influence on Organizational Performance and Sustained Competitive Advantage. This research also provides discussion on the findings as well as limitations, theoretical and practical contributions, theoretical and managerial implications of the study, and suggestions for future research.